PENYULUHAN DAN WORKSHOP BAHAN ALAM “SEJAHTERAKU” (SERBUK JAHE MERAH, TEMULAWAK, SERAI, KUNYIT) UNTUK MENINGKATKAN IMUNITAS DI MASA PANDEMI DI KELURAHAN GILINGAN KECAMATAN BANJARSARI TAHUN 2022 : PENYULUHAN DAN WORKSHOP BAHAN ALAM “SEJAHTERAKU” (SERBUK JAHE MERAH, TEMULAWAK, SERAI, KUNYIT) UNTUK MENINGKATKAN IMUNITAS DI MASA PANDEMI DI KELURAHAN GILINGAN KECAMATAN BANJARSARI TAHUN 2022 (Jurnal Mitra Masyarakat (JMM), 2022)
The outbreak of Coronavirus Disease 2019 (Covid-19) is one of the infectious diseases that currently become the global public health crisis. The first case of Covid-19 was reported by World Health Organization (WHO) on December 31, 2019 from Wuhan, China. As an alternative to improve the immune system of the population in Gilingan Village, ingredients from traditional plants made in the form of powder instant are made easily and cheaply. Red ginger combined with temulawak, turmeric and lemongrass is made in the form of powder instant with the addition of sugar as a preservaton. The target of the counseling activity on Covid-19 is the community ofGilingan Village, Banjarsari, Surakarta where from each RW would send 1 representative to take part in the counseling. Method implementation devotion that is with counseling about Covid-19 and counseling utilization ofnatural ingredients that are useful for increasing the immune system packaged in instant powder preparations as well as demonstrations. Data analysis in this activity uses the Paired Sample t Test with SPSS, where this analysis uses pre-test and post-test values. From the output of the paired samples test, the Sig value is obtained. (2-tailed) of 0.000 < 0.05. So it can be concluded that there is an influence in the community service program, namely counseling and workshops on my welfare (red ginger powder, temulawak, lemongrass, turmeric) that have been carried out.